Report of the Workshop on the Comprehensive Assessment of Right Whales: A Worldwide Comparison - Int, IWC (J. Cetacean Res. Manage., 2020)
The Workshop was held at the Monkey Valley Beach Resort near Cape Town, South Africa from 19-25 March 1998. It was preceded by a two-day Symposium at the Two Oceans Aquarium, Cape Town.